2018
DOI: 10.1016/j.celrep.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

A Dimerization Function in the Intrinsically Disordered N-Terminal Region of Src

Abstract: SUMMARYThe mode of regulation of Src kinases has been elucidated by crystallographic studies identifying conserved structured protein modules involved in an orderly set of intramolecular associations and ligand interactions. Despite these detailed insights, much of the complex behavior and diversity in the Src family remains unexplained. A key missing piece is the function of the unstructured N-terminal region. We report here the function of the N-terminal region in binding within a hydrophobic pocket in the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 81 publications
3
62
0
Order By: Relevance
“…It may be possible that Src kinases dock and rely on a specific dimeric motif of associated FcγRIIIa and adapters for the kinases to dimerize themselves and auto phosphorylate, structurally similar to what has been shown for the JAK2 kinases ( 188 ). Indeed, Src dimerization is predicted to be necessary as its role as a hub for multiple signaling activities ( 189 191 ).…”
Section: Geometric and Spatial Considerations Within The Nkismentioning
confidence: 99%
“…It may be possible that Src kinases dock and rely on a specific dimeric motif of associated FcγRIIIa and adapters for the kinases to dimerize themselves and auto phosphorylate, structurally similar to what has been shown for the JAK2 kinases ( 188 ). Indeed, Src dimerization is predicted to be necessary as its role as a hub for multiple signaling activities ( 189 191 ).…”
Section: Geometric and Spatial Considerations Within The Nkismentioning
confidence: 99%
“…In addition to improve the spatial resolutionof CRY2-system 12 , engineering OS revealed new functions of SRC conformational intermediates or domains. Despite being mostly described as a monomer, SRC can dimerize and oligomerize after opening of its conformation 8,10 . In addition to the SH2 domain mediated regulation for SRC focal adhesion targeting, our synthetic OS revealed that SRC oligomerization is a stabilizing process in adhesive sites mediated by SH3 domains.…”
Section: Engineering Synthetic Src To Understand Its Complex Structurmentioning
confidence: 99%
“…Second, interactions with lipids add an additional layer of complexity by affecting the binding capacities of the poorly structured UD and SH3 domains 7 . Third, this complexity also includes the level of clustering of this kinase while being able to oligomerized from the poorly knowns c-SRC dimers to 80 nm-nanoclusters of c-SRC molecules [8][9][10] . The vast amount of SRC conformational intermediates suggests that c-SRC signaling emerges from a heterogeneous population of molecules with different levels of kinase activity targeting dynamically a repertoire of interactors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has suggested that the myristoyl group could also interact with the kinase domain of a second Src molecule to form a dimer [54]. The intermolecular interaction of the Src kinase domain with a N-terminal myristoyl group is expected to be promiscuous.…”
Section: The Disordered Region Of Src Family Kinases: Fuzzy Complexesmentioning
confidence: 99%